High‐Entropy Alloy/Intermetallic Compound Heterostructures for Efficient Hydrazine Oxidation‐Assisted Hydrogen Production - Shi, Hang; Dai, Tian‐Yi; Sun, Xin‐Ying; Zhou, Zhi‐Lan; Wang, Ying; Zeng, Shu‐Pei; Wang, Tong‐Hui; Han, Gao‐Feng; Wen, Zi; Fang, Qian‐Rong; Lang, Xing‐You; Jiang, Qing (Advanced materials (Weinheim), 2025)
Configuring integrative catalytic heterostructures is an efficient strategy to circumvent the universal linear scaling relationships for accelerating multiple‐intermediate redox reactions. Here this study reports nonprecious metal‐based high‐entropy alloy/intermetallic compound heterostructure with a 3D nanoporous architecture as a high‐performance electrocatalyst for hydrazine oxidation reaction. By making use of strain engineering of hexagonal close‐packed multicomponent intermetallic compound core, high‐entropy NiFeCoCuCrMn alloy surface is comprised of multiple active centers with undulatory adsorption energies, which enable *N 2 H x intermediate spillover to adjust rate‐determining step and lower kinetic barriers. As a consequence of nanoporous architecture endowing abundant multiple active surfaces, this heterostructure mediates hydrazine electrooxidation of as high as ampere‐level current densities at >0.08 V versus reversible hydrogen electrode, showing genuine potential to replace sluggish oxygen evolution reaction for hydrogen production via water electrolysis. Its hydrazine oxidation‐assisted water electrolyser delivers 500 mA cm −2 at ultralow cell voltage of 0.87 V, and maintains exceptional stability for 1000 h.